Civil engineers for management proceedings of a conference organized by the Institution of Civil Engineers and held in London on 6-7 November 1986. (Thomas Telford, 1987)
Needs of employer's involved in management in the civil engineer field and satisfying the needs are discussed in these papers. They conclude with what can be learned from others and what steps should be taken next.